URBAN CULTURAL OMNIVORES, UPSCALING ETHNIC FOOD AND CULINARY REPRODUCTION IN MARCO AND SUNTIANG - Tambunan, Shuri Mariasih Gietty; Widhiasti, Maria Regina; Bachrioktora, Yudi; Utami, Nila Ayu (UI Scholars Hub, 2019)
Culinary practices have always been considered as social and cultural activities signifying ideas of continuity and transformation regarding one‟s culture and identity. As migration happens, people move from their hometown and recreate familiar food and flavors in their new home. Therefore, the study of culinary practices will reveal the dynamics of constant negotiation between having to trace back the familiar taste, for example by using inherited recipes, with the necessity to innovate and reproduce meals from their hometown with new ingredients and materials found in the new place. Furthermore, in an urban setting that has been heavily influenced with a variety of culinary practices from other locales in Indonesia or from other countries, culinary practices in Jakarta could no longer be analyzed as merely everyday activities as they have become an arena of contestation and negotiation. This research discusses how two up-scale restaurants, Suntiang (a Padangnese-Japanese fusion restaurant) and Marco (a self-proclaimed Padang peranakan restaurant), re-inscribe Padangnese cuisines and make new meanings on „old‟ traditional delicacies.